Simulating Financial Risks on the Basis of Statistical Assessment Methods - N. PARFENTSEVA; H. HOLUBOVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
Financial risks are summed up by type and form, macro- and micro-level. The importance of monitoring of financial risks in insurance, banking, monetary activities and various business processes is substantiated. It is emphasized that the sound assessment of risks constitutes an important tool in risk management. The essence, advantages and disadvantages of selected methods for financial risk assessment is shown: Value-at-Risk, Monte Carlo method, methods based on IRB approach, Shortfall, LDA, methods using Bayesian programming.The importance of statistical methods for the assessment of financial risks like non-parametric techniques of Kaplan – Meier and Cox proportional hazards model is substantiated. It is emphasized that the cumulative hazard function by Cox model reflects the cumulative level of bank losses, hence, its application in risk assessment is capable to protect and warn the bank about a potential threat. Kaplan – Meier method allows to assess the probability of risk occurrence and risk level in various client groups, which is a necessary component of risk monitoring. But its drawback is its incapability to account for several risks at the same time. In view of this, a sounder method for risk assessment is Cox proportional hazard regression. The input data for constructing this regression can include both categorical and continuous variables, thus enabling for accounting of a multiplicity of risk-related factors.    It is concluded that Kaplan – Meier method should be used with caution, because the survival function may overvalue the probability of occurrence of “critical” event, depending on the internal nature of data and their individual variances. Hence, applications of semiparametric techniques of Cox proportional hazards model should be an alternative approach to the survival analysis.